Characterisation of a Live-Attenuated Rabies Virus Expressing a Secreted scFv for the Treatment of Rabies - Samuel P. Smith; Rebecca Shipley; Pascal Drake; Anthony R. Fooks; Julian Ma; Ashley C. Banyard (Viruses, 2023)
Rabies virus (RABV) causes possibly the oldest disease and is responsible for an estimated >59,000 human fatalities/year. Post exposure prophylaxis (PEP), the administration of vaccine and rabies immunoglobulin, is a highly effective tool which is frequently unavailable in RABV endemic areas. Furthermore, due to the constraints of the blood-brain barrier, current PEP regimes are ineffective after the onset of clinical symptoms which invariably result in death. To circumvent this barrier, a live-attenuated recombinant RABV expressing a highly RABV-neutralising scFv antibody (62-71-3) linked to the fluorescent marker mCherry was designed. Once rescued, the resulting construct (named RABV-62scFv) was grown to high titres, its growth and cellular dissemination kinetics characterised, and the functionality of the recombinant 62-71-3 scFv assessed. Encouraging scFv production and subsequent virus neutralisation results demonstrate the potential for development of a therapeutic live-attenuated virus-based post-infection treatment (PIT) for RABV infection.